Temperature-dependent raman spectroscopy of titanium trisulfide (TiS3) nanoribbons and nanosheets - Pawbake, Amit S.; Island, Joshua O.; Flores, Eduardo; Ramon Ares, Jose; Sanchez, Carlos; Ferrer, Isabel J.; Jadkar, Sandesh R.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; Late, Dattatray J. (ACS Applied Materials & Interfaces, 2015)
Titanium trisulfide (TiS3) has recently attracted the interest of the 2D community because it presents a direct bandgap of similar to 1.0 eV, shows remarkable photoresponse, and has a predicted carrier mobility up to 10000 cm(2) V-1 s(-1). However, a study of the vibrational properties of TiS3, relevant to understanding the electron-phonon interaction that can be the main mechanism limiting the charge carrier mobility, is still lacking. In this work, we take the first steps to study the vibrational properties of TiS3 through temperature-dependent Raman spectroscopy measurements of TiS3 nanoribbons and nanosheets. Our investigation shows that all the Raman modes linearly soften (red shift) as the temperature increases from 88 to 570 K due to anharmonic vibrations of the lattice, which also includes contributions from the lattice thermal expansion. This softening with the temperature of the TiS3 modes is more pronounced than that observed in other 2D semiconductors, such as MoS2, MoSe2, WSe2, and black phosphorus (BP). This marked temperature dependence of the Raman spectra could be exploited to determine the temperature of TiS3 nanodevices by using Raman spectroscopy as a noninvasive and local thermal probe. Interestingly, the TiS3 nanosheets show a stronger temperature dependence of the Raman modes than the nanoribbons, which we attribute to lower interlayer coupling in the nanosheets.
Keywords: 2D semiconductors; layered materials; Raman spectroscopy; thermal effect; TiS3 nanoribbons; TiS3 nanosheets